Dirt, Undress, and Difference : Critical Perspectives on the Body's Surface. - Masquelier, Adeline (Indiana University Press, 2005)
While there is widespread interest in dress and hygiene as vehicles of cultural, moral, and political value, little scholarly attention has been paid to cross-cultural understandings of dirt and undress, despite their equally important role in the fashioning of identity and difference. The essays in this absorbing and thought-provoking collection contribute new insights into the neglected topics of bodily treatments and transgressions. In detailed ethnographic studies from around the world, the contributors recast assumptions about filth and nakedness, exploring how various forms of transgre.